KERUMUNAN HARGA SAHAM PADA MULTIFRAKSI - Purwoto, Lukas (Benefit: Jurnal Manajemen dan Bisnis, 2009)
Price clustering is the tendency of prices to be observed more often at some numbers than others. This study documents the existence and persistence of stock price clustering on the Jakarta Stock Exchange.Over the period from 2001 to 2004, daily closing stock prices are found to cluster at 00 followed by 50. Significant clustering within each different thick sizes is found in transaction prices as well as in order prices and remarkably persistent through all trading days. Moreover, stock price clustering is found to increase with volatility, and decrease with transaction frequency.